History and Industry Location: Evidence from German Airports - Redding, Stephen J.; Sturm, Daniel M.; Wolf, Nikolaus (The Review of Economics and Statistics, 2011)
A central prediction of a large class of theoretical models is that industry location is not uniquely determined by fundamentals. Despite the theoretical prominence of this idea, there is little systematic evidence in support of its empirical relevance. This paper exploits the division of Germany after World War II and the reunification of East and West Germany as an exogenous shock to industry location. Focusing on a particular economic activity, an air hub, we develop a body of evidence that the relocation of Germany's air hub from Berlin to Frankfurt in response to division is a shift between multiple steady states.